2018
DOI: 10.1177/1744806918817975
|View full text |Cite
|
Sign up to set email alerts
|

Evoked hypoalgesia is accompanied by tonic pain and immune cell infiltration in the dorsal root ganglia at late stages of diabetic neuropathy in mice

Abstract: Diabetic peripheral neuropathy is a major debilitating late complication of diabetes, which significantly reduces the quality of life in patients. Diabetic peripheral neuropathy is associated with a wide spectrum of sensory abnormalities, where in loss of sensation or hypoalgesia to applied external stimuli is paradoxically accompanied by debilitating tonic spontaneous pain. In numerous studies on animal models of diabetic peripheral neuropathy, behavioural measurements have been largely confined to analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…The role of T-cells in chronic neuropathic and inflammatory pain states is an area of active research ( Laumet et al, 2019 ). T-cells contribute to the generation and maintenance of neuropathic pain by infiltrating into the nervous system days to weeks post-nerve injury ( Moalem et al, 2004 , Agarwal et al, 2018 ). First, they infiltrate the site of injury and the spinal nerve, then the DRG, and finally the SDH ( Moalem et al, 2004 ).…”
Section: Regulation Of Lat1 By the Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
“…The role of T-cells in chronic neuropathic and inflammatory pain states is an area of active research ( Laumet et al, 2019 ). T-cells contribute to the generation and maintenance of neuropathic pain by infiltrating into the nervous system days to weeks post-nerve injury ( Moalem et al, 2004 , Agarwal et al, 2018 ). First, they infiltrate the site of injury and the spinal nerve, then the DRG, and finally the SDH ( Moalem et al, 2004 ).…”
Section: Regulation Of Lat1 By the Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
“…Based on the data that neutrophil-depleted mice did not show mechanical allodynia, it is evident that neutrophils certainly play an important role in the generation of mechanical allodynia during the preclinical phase of EAE. Naïve mice never show mechanical allodynia under physiological condition, although neutrophils are located in the DRG 37 . Distinct from previous data, we could not observe MPO/NE immunoreactivity in the DRG of sham mice.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have used rodent models to evaluate hypoalgesia. Thermal hypoalgesia in rodents has been observed in the late stage of STZ-induced type I diabetic models [ 47 , 51 , 58 , 59 , 60 , 61 , 62 ] and in various type II diabetic models, including the HFD-induced diabetic model and db/db mice [ 63 , 64 , 65 ]. Here, we confirmed the paradoxical alteration of pain perception, such as hyperalgesia and hypoalgesia/hypoesthesia in the type II HFD- or db/db model and type I STZ-model.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we confirmed the paradoxical alteration of pain perception, such as hyperalgesia and hypoalgesia/hypoesthesia in the type II HFD- or db/db model and type I STZ-model. Notably, many studies revealed that hyperalgesia occurs at the early stage after STZ-treatment(s), and hypoalgesia does several weeks later, though the timing showing the transition from hyperalgesia to hypoalgesia depends on the experimental models [ 47 , 51 , 58 , 61 , 62 ]. In the present study, we observed significant thermal hyperalgesia in HFD-, db/db- and STZ-models, but failed to detect the thermal hypoalgesia by the time of 10 weeks after the start of HFD-treatments, or 49 days (7 weeks) after STZ-treatment.…”
Section: Discussionmentioning
confidence: 99%